Systematic literature review of hospital medication administration errors in children - Ameer A; Dhillon S; Peters MJ; Ghaleb M (Dove Medical Press, 2015)
Ahmed Ameer,1 Soraya Dhillon,1 Mark J Peters,2 Maisoon Ghaleb11Department of Pharmacy, School of Life and Medical Sciences, University of Hertfordshire, Hatfield, UK; 2Paediatric Intensive Care Unit, Great Ormond Street Hospital, London, UK Objective: Medication administration is the last step in the medication process. It can act as a safety net to prevent unintended harm to patients if detected. However, medication administration errors (MAEs) during this process have been documented and thought to be preventable. In pediatric medicine, doses are usually administered based on the child's weight or body surface area. This in turn increases the risk of drug miscalculations and therefore MAEs. The aim of this review is to report MAEs occurring in pediatric inpatients. Methods: Twelve bibliographic databases were searched for studies published between January 2000 and February 2015 using “medication administration errors”, “hospital”, and “children” related terminologies. Handsearching of relevant publications was also carried out. A second reviewer screened articles for eligibility and quality in accordance with the inclusion/exclusion criteria. Key findings: A total of 44 studies were systematically reviewed. MAEs were generally defined as a deviation of dose given from that prescribed; this included omitted doses and administration at the wrong time. Hospital MAEs in children accounted for a mean of 50% of all reported medication error reports (n=12,588). It was also identified in a mean of 29% of doses observed (n=8,894). The most prevalent type of MAEs related to preparation, infusion rate, dose, and time. This review has identified five types of interventions to reduce hospital MAEs in children: barcode medicine administration, electronic prescribing, education, use of smart pumps, and standard concentration. Conclusion: This review has identified a wide variation in the prevalence of hospital MAEs in children. This is attributed to the definition and method used to investigate MAEs. The review also illustrated the complexity and multifaceted nature of MAEs. Therefore, there is a need to develop a set of safety measures to tackle these errors in pediatric practice. Keywords: medication administration errors, children's hospital, pediatric, nature, incidence, intervention